Perlindungan Hukum terhadap Disabilitas dalam Memenuhi Hak Mendapatkan Pendidikan dan Pekerjaan - Jazim Hamidi (Jurnal Hukum IUS QUIA IUSTUM, 2016)
As a law-based country, it becomes a must for Indonesia to protect the disability; one of constitutional rights as regulated in Article 28 I Sentence (2) Constitution 1945 of Indonesia Republic. This research is to study: first, the form of the legal protection in an attempt to fulfil the right for getting education and job for the disabilities; second, the formulation of the affirmative action policy for the accessibility in education and job for the disabilities in Indonesia. the typology of this research is the dogmatic legal research addressed to observe and formulate the legal argumentation through the analysis on the core of the issues. The technique of collecting the legal material was done through the library research and the approach used was the statute approach that is by analysing the valid legal regulation regarding the disabilities. This research concluded that first; the government tends to give the legal protection discriminatively for those with disabilities to obtain the proper education and job. Second, there was a bias in legal norm in the regulation on the accessibility of education and job; thus there is a need of legal renewal in the form of affirmative action policy on accessibility of education and job for the disabilities including: 1) completing (making something better); 2) changing to make it much better and 3) doing something unavailable before